The Reality of Applying BSC Approach and the Obstacles to Its Application in Islamic Banks in Palestine - Abueid, Raed (International Journal of Islamic Banking and Finance Research, 2020)
The research aimed to recognize the reality of the application of the Balanced Scorecard (BSC) Approach and the Obstacles applied in the Islamic banks in Palestine. The researcher has designed a questionnaire composed of two dimensions, then the questionnaire was distributed to male and female employees in Islamic banks operating in the Hebron district, Data were statistically analyzed by the SPSS program , The study concluded that the reality of the application of Balanced Scorecard  Approach in Islamic banks was High in general on all dimensions of the study, and that the most important obstacles to the application of the Balanced Scorecard (BSC )Approach in these banks are the lack of knowledge of these banks and the benefits of the application of this approach, In addition to the high cost of implementation and the lack of qualified personnel to implement it, The study recommended the need for attention and increase Islamic banks in focusing on the application of this approach because of its advantages which are beneficial to the banks , customers and the community in general and  its adoption in the marketing strategies, and that Islamic banks should work to intensify its efforts to develop and improve banking services to keep up with developments in the world.